Investigations on the interplays between Schistosoma mansoni, praziquantel and the gut microbiome - Pierre H. H. Schneeberger; Jean T. Coulibaly; Gordana Panic; Claudia Daubenberger; Morgan Gueuning; Jürg E. Frey; Jennifer Keiser (Parasites & Vectors, 2018)
Abstract Background Schistosomiasis is a neglected tropical disease burdening millions of people. One drug, praziquantel, is currently used for treatment and control. Clinically relevant drug resistance has not yet been described, but there is considerable heterogeneity in treatment outcomes, ranging from cure to only moderate egg reduction rates. The objectives of this study are to investigate potential worm-induced dysbacteriosis of the gut microbiota and to assess whether a specific microbiome profile could influence praziquantel response. Methods Using V3 and V4 regions of 16S rRNA genes, we screened the gut microbiota of 34 Schistosoma mansoni infected and uninfected children from Côte d’Ivoire. From each infected child one pre-treatment, one 24-hour and one 21-day follow-up sample after administering 60 mg/kg praziquantel or placebo, were collected. Results Overall taxonomic profiling and diversity indicators were found to be close to a “healthy” gut structure in all children. Slight overall compositional changes were observed between S. mansoni-infected and non-infected children. Praziquantel treatment was not linked to a major shift in the gut taxonomic profiles, thus reinforcing the good safety profile of the drug by ruling out off-targets effects on the gut microbes.16S rRNA gene of the Fusobacteriales order was significantly more abundant in cured individuals, both at baseline and 24 hours post-treatment. A real-time qPCR confirmed the over-abundance of Fusobacterium spp. in cured children. Fusobacterium spp. abundance could also be correlated with treatment induced S. mansoni egg-reduction. Conclusions Our study suggests that neither a S. mansoni infection nor praziquantel administration triggers a significant effect on the microbial composition and that a higher abundance of Fusobacterium spp., before treatment, is associated with higher efficacy of praziquantel in the treatment of S. mansoni infections. Trial registration International Standard Randomised Controlled Trial, number ISRCTN15280205.